Sindrom Rapunzel: Laporan Kasus - Khairun Nisa Berawi; Fauziyyah Nuur Al Azizah (Jurnal Ilmu Medis Indonesia, 2022)
Purpose: This study aimed to summarize the general history, physical exam findings, confirmation test, and treatment of a patient with rapunzel syndrome. Research Methodology: This article is a pediatric surgery RSUD Abdoel Moeloek Lampung case report in 11 March 2020. The subject of the case is a 11-year-old girl who is hospitalized in the hospital ward with Rapunzel syndrome. Result: A 11-year-old girl, an inpatient in the Pediatric surgery Ward, RSUD Abdoel Moeloek Lampung, with abdominal pain such as squeezing, nausea and vomiting filled with water and hard and little bowel movements.. On physical examination, bloated abdomen, epigastric tenderness and left hypochondrium, mass (+).on ct scan examination with gastric contrast looks enlarged, isodense lesions appear, irregular edges in the gastric lumen to the duodenum, separated from the wall, post contrast does not appear enhanced. The patient was clinically diagnosed with “Rapunzel Syndrome.” Management of the patient during treatment was upper midline laparatomy. Limitations: This case report is limited to rapunzel syndrome cases with a scarce number of cases and rare cases in children. Contribution: This case report can be helpful in medical education or used as a reference in making relevant case reports and can be applied in the hospital area when there are cases of Rapunzel syndrome.